Kenya's agrifood system: Structure and drivers of transformation - Xinshen Diao; Pauw, Karl; Smart, Jenny; Thurlow, James (International Food Policy Research Institute, 2023)
This analysis is composed of two parts. The evolving structure of Kenya’s agrifood system (AFS) and its contribution to national development is assessed using a series of Social Accounting Matrixes (SAMs) for Kenya for the period 2009–2019. Economic performance is also assessed at subsector level to better understand the contributions of different agrifood value chains to Kenya’s development and economic transformation in recent years. The analysis reveals that the effects of AFS transformation stretches well beyond primary agriculture, creating jobs and income opportunities throughout the economy. In fact, the off-farm components of the AFS have grown more rapidly than primary agriculture, although differences in market structure and internationally tradable status contributed to varied patterns of growth across value chains. The analysis further reveals that it is the domestic market, not exports, that has driven the recent growth in Kenya’s AFS. Rapid urbanization and increased incomegenerating opportunities in the rural nonfarm sector are causing dietary patterns to shift, which will continue to shape the transformation of the AFS in Kenya. A forward-looking analysis using IFPRI’s Rural Investment and Policy Analysis (RIAPA) model – an economywide modeling framework – assesses the potential impacts of future value chain growth on development outcome indicators. The findings reveal that value chains differ considerably in their effectiveness in achieving various development outcomes. Promoting only one value chain may also result in trade-offs across these development goals. For example, the coffee and tea value chains are highly effective at raising off-farm employment in the AFS, but they have weak impacts on diet quality. Likewise, cattle and dairy have strong off-farm GDP effects within the AFS, but are relatively ineffective at reducing poverty. By promoting and investing in several value chains simultaneously, policymakers can leverage synergies and mitigate trade-offs across development outcomes associated with specific value chains. The RIAPA analysis here suggests that joint promotion of the pulses and oilseeds, fruits and nuts, and cattle and dairy value chains will be most effective at impacting the full spectrum of development outcomes tracked in the model, including poverty, growth, jobs, and diets. However, the final value chain selection may change depending on the importance policymakers attach to the respective development outcomes.